Application of an analytical method for the design for robustness of RC flat slab buildings. (1st May 2022) - Martinelli, Paolo; Colombo, Matteo; Ravasini, Simone; Belletti, Beatrice
Highlights: Design for robustness of multi-story RC frame with RC flat slabs. The analytical strip method was validated with experimental and NLFE results. The capability of the analytical method to predict the behaviour at the catenary stage was proved. The analytical method provides the ultimate bearing capacity and the failure modes of a large variety of flat slabs. The paper provides, in the form of design nomographs, the maximum load in accidental design situation. Abstract: Nowadays the structural engineering community needs reliable and design-oriented methods for the design of low and medium-rise reinforced concrete (RC) buildings with regard to progressive collapse. In this context, the current work aims to validate and apply a new analytical method suitable for the design for robustness of RC buildings characterised by the presence of flat slabs falling in low and medium consequence classes. The analytical method presented in this study is an extension of a method recently proposed by some of the authors for the analysis of two-way slabs in which flexural capacity and punching and post-punching failure criteria are added to reproduce the ultimate behaviour of flat slabs. In this paper, the design for robustness is applied together with the design for ultimate and serviceability limit states in the framework of the partial safety factor method of verification for RC flat slabs. The analytical method is applied as a direct method to evaluate the level of robustness of RC flat slabs to sustain a localised failure simulated by considering an internal column removal scenario. First, the method is validated by comparing the analytical results with both experimental data available in the literature and nonlinear finite element results obtained by adopting a multi-layered shell element approach and the PARC_CL 2.0 crack model. The comparison of the results demonstrates the reliability of the analytical approach in reproducing the ultimate load and ultimate chord rotation of flat slabs with a good approximation by considering the effect of tensile membrane action (TMA). Second, in strategies based on unidentified accidental actions, the analytical method is used to carry out a parametric analysis in the context of an internal column loss scenario. The parametric analysis allows the level of robustness to be evaluated by varying the main geometrical properties that affect the failure mode, resistance and ductility of RC flat slabs. Finally, the paper presents—for a given span and span-to-depth ratio—the required reinforcement ratios, design load in the accidental load combination and ultimate chord rotation in the form of design nomographs useful for engineering.